Retarding the corrosion of iron by inhomogeneous magnetic fields. Issue 8 (16th January 2013) - Sueptitz, R.; Tschulik, K.; Uhlemann, M.; Eckert, J.; Gebert, A.
<x xml:space="preserve">Abstract</x> The influence of a magnetic field yielding high magnetic flux densities and high flux density gradients on the free corrosion behavior of iron in a low concentrated acidic solution with and without chloride ions is studied by long time exposure experiments and electrochemical impedance spectroscopy (EIS). A decrease of the corrosion rate in electrode surface regions of high magnetic flux density is detected. This decrease of the dissolution rate is significantly stronger in the presence of chloride ions. The observed effects are discussed on the basis of the magnetically induced forces acting on the ions present in the solution, the surface coverage fraction of adsorbed species, and the stability of these adsorbed species.